Nomophobia Sebagai Determinan Kualitas Tidur Mahasiswa Keperawatan - Irnanda Naufal Riandi; Wastu Adi Mulyono; Hasby Pri Choiruna (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background. Sleep is a basic human need that has to be fulfilled as a fundamental of physiological part, but mostly need of sleep not fulfil enough and have a bad sleep quality. There are numerous factors that affect someone sleep quality, those are age, gadget, nomophobia, and physical activity. This research purposed to predict the most influential variable of sleep quality among nursing students. Methods. This cross-sectional study aimed to predict the influential variable that affect sleep quality among nursing students. Regression analysis to 80 respondents that selected by simple random sampling from students batch 2019, 2020, 2021, and 2022 had done to examine the determinant of sleep quality nursing students. Results. From four predictors that used in this research, only nomophobia (p=0,001) which had a significant correlation to sleep quality by partial t test. Simultaneous F test indicated that all variable were significantly correlated with sleep quality (p=0,004) and coefficient determination 18,1% . Simple linear regression with nomophobia and sleep quality get significant result (p=0,001) and coefficient determination 0,171. Conclusion. Nomophobia is a determinant variable of sleep quality among nursing academic community. Sleep problem among nursing students around a fifth affected by nomophobia. It is suggested to nursing student aware of their anxiety to gadget because it might help for better sleep quality.